2022
DOI: 10.1109/access.2022.3228392
|View full text |Cite
|
Sign up to set email alerts
|

Few-Shot PCB Surface Defect Detection Based on Feature Enhancement and Multi-Scale Fusion

Abstract: In printed circuit board (PCB) defect detection, it is difficult to collect defect samples, and the detection effect is poor due to the lack of data. On the basis of the few-shot learning method, a few-shot PCB defect detection model is proposed. This model introduces feature enhancement module and multiscale fusion module. The feature enhancement module based on the improved convolution block attention module (CBAM) can highlight the key areas of the received feature maps and suppress the interference of usel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Wang et al [38] propose a PCB defect detection model with a few-shot learning that gives possibilities for usage of small datasets and to achieve good performance. The model includes modules for feature enhancement and multiscale fusion with the goal the model precision to be improved and small object defects to be detected.…”
Section: Research Related To Defects Detection On Pcb and Pcbamentioning
confidence: 99%
“…Wang et al [38] propose a PCB defect detection model with a few-shot learning that gives possibilities for usage of small datasets and to achieve good performance. The model includes modules for feature enhancement and multiscale fusion with the goal the model precision to be improved and small object defects to be detected.…”
Section: Research Related To Defects Detection On Pcb and Pcbamentioning
confidence: 99%
“…Furthermore, in [12], the potentiality of a model developed by the authors was demonstrated through extensive experiments on a PCB dataset (i.e., FSOD professional few-shot object detection dataset created by Tencent in 2020), indicating the potential for innovative approaches to defect detection. In [13], the authors also focused on utilizing deep learning, specifically a skip-connected convolutional autoencoder, for PCB defect detection, emphasizing the criticality of surface inspection in ensuring quality control.…”
Section: Introductionmentioning
confidence: 99%